Religion, secular beliefs, and human rights - Lerner, Natan (Studies in religion, secular beliefs, and human rights ;, 2012)
Religion, and beliefs related to religion, are a central factor in international life and politics. International law, and human rights law in particular, have to take into consideration the religious dimension, and have done it to some extent. A body of positive law has already been developed for the protection of freedom of religion, and from religion, by the United Nations and regional and specialized organizations. The first edition of this book appeared six years ago, in coincidence with the 25th anniversary of the 1981 United Nations Declaration on the Elimination of All Forms of Intolerance and Discrimination Based on Religion of Belief. It discussed the legal meaning of religion and belief, the United Nations work in this respect, religious minorities, relevant regional and special arrangements, the issue of proselytism, religion and terrorism, religious symbols, international criminal law, and some particular cases such as the state and religious communities in Israel, and this country's agreement with the Holy See. This second edition of the book updates the information on relevant developments that took place in the time elapsed. and incorporates several new chapters on important issues related to religious freedoms. Such are the chapters on freedom from religion, religion and freedom of association, religion and freedom of expression (including the controversy with respect of defamation of religions), and group rights and legal pluralism. The order of the chapters has been rearranged. It is hoped that law and political science schools, human rights associations and scholars, as well as governments and bodies active in the area of religious freedoms, will find interest in this second, revised and considerably enlarged, edition.